Plakat "Jean Vincent Conseiller national - député Parti du Travail"
politischer Rahmen;Parlament;Parlamentsebene;nationales Parlament;Nationalrat politischer Rahmen;Wahlen und Abstimmungen;Wahl;Parlamentswahl;Nationalratswahl politischer Rahmen;politische Partei (allgemein);politische Partei (speziell);PdAdS